With Us Always: A History of Private Charity and Public Welfare - Critchlow, Donald T.; Parker, Charles H. (Rowman & Littlefield Publishers, 1998)
Although welfare reform is currently the government's top priority, most discussions about the public's responsibility to the poor neglect an informed historical perspective. This important book provides a crucial examination of past attempts, both in this country and abroad, to balance the efforts of private charity and public welfare. The prominent historians in this collection demonstrate how solutions to poverty are functions of culture, religion, and politics, and how social provisions for the poor have evolved across the centuries.